Experiencias, significados y percepciones sobre la política de alimentación escolar y las contribuciones a la seguridad alimentaria y nutricional y la calidad de vida de niños y niñas de una ciudad de Argentina - Daniela Moyano; Elizabeth Raquel Rodríguez; Nilda Raquel Perovic (Revista Española de Nutrición Humana y Dietética)
Introduction: given the current context of malnutrition and difficulties of access to food (food price inflation) reported in different countries and continents, school feeding policies have a central role to play. This article explores the experiences, meaning, and perceptions from teacher perspective on the school feeding policy (SFP) in Cordoba, Argentina, 2018.